Pengembangan Produk UMKM Gethuk Singkong Menjadi Keripik Gethuk Melalui Inovasi Kemasan Dan Label - Dhea Nisa, Fytria Pramitha; Wiyandani, Jesika Ersa; Herdaningrum, Wahyu Purwo; Agianto, Ucuk (CV. Edutechnium Indonesia, 2024)
Poko Village is located in the Jambon sub-district of Ponorogo Regency, and the main livelihood of the people in Poko Village is as farmers and small business actors. Most of the agricultural output consists of cassava, which serves as the main raw material for small and medium enterprises (SMEs), one of which processes it into gethuk. One of the challenges faced by these cassava gethuk SMEs is the lack of innovation in developing their products and creating packaging that can attract consumers. This research aims to develop the MSME product of cassava gethuk into gethuk chips by innovating the packaging and label. The research was conducted in the production area of MSMEs in Poko Village, Jambon District, Ponorogo. The method used in this research is the product development method, which includes the stages of design, production, and product evaluation. The results of the study indicate that innovations in packaging and labeling for gethuk chips can enhance product appeal and expand the market by means such as selling through e-commerce. Gethuk chips with attractive packaging and labeling are expected to become a typical souvenir product from Ponorogo.